Perancangan Sistem Otomatisasi Penyalaan Lampu, Kipas Angin, dan Proyektor Dalam Ruang Kelas - Rinaldi, Reza Satria; Lase, Yosri Riadi; Rosa, M. Khairul Amri (UNIB Press, 2021)
In general, the control of using electronic equipment in the classroom manually. Sometimes lecturers or students forget to turn off electronic equipment after the class so that there is a waste of electrical energy use. Application of automation of using electronic equipment is one solution to overcome these problems so that electrical energy becomes more efficient. This study designed a prototype of an automation system for electrical equipment in the classroom, namely lights, fans, and projectors. This system was also to turn off the electricity when nobody was in the class. The automation system controls the use of electrical energy in devices in the classroom through on-off control of the electrical network components connected to each device. In this design, the PIR sensor can detect the presence of people up to a distance of 7 meters. The Arduino Uno controller activates the lights in the class when the LDR Sensor detects a light intensity of less than 200 Lux. Then, the fan is active when the LM35 sensor detects the temperature in the class above 28oC. The FC-04 sensor detects the sound of clapping for control of projector ignition by the controller.